Beyond Difficult Co-Workers: How Individual Characteristics‎Shape Negative Encounter Attitudes and Turnover Intention in ‎Service Organizations - Setiawan, Abdi; Lubis, Arlina Nurbaity; Absah, Yeni; Sembiring, Beby Karina F (International Journal of Accounting and Economics Studies, 2025)
Despite organizational turnover costs reaching 20-200% of annual salary per departing employee, the mechanisms driving departure intentions in collectivist cultures remain poorly understood. This study examines how Difficult Co-workers (DCW) and Individual Characteristics (IC) influence Turnover Intention (TI) through Negative Encounter Attitudes (NEA) among Indonesian hotel employees. Using social ‎exchange theory, we surveyed 258 employees across 25 three-star hotels in Medan, Indonesia, analyzing data through PLS-SEM to test ‎direct relationships and mediation effects. Findings challenge conventional assumptions about workplace relationships. Individual character-‎istics strongly predict negative encounter attitudes (β = 0.931, p < 0.05), while difficult co-workers surprisingly do not (β = 0.053, p > ‎‎0.05). Both variables influence turnover intention via distinct pathways—difficult colleagues directly increase departure likelihood (β = ‎‎0.445, p < 0.001), whereas certain individual traits appear protective (β = -0.287, p < 0.05). Crucially, negative encounter attitudes mediate ‎only the individual characteristics-turnover relationship (β = 0.371, p < 0.05), indicating fundamentally different causal mechanisms. Cross-sectional design and geographic limitation restrict generalizability, necessitating longitudinal validation across diverse contexts. These patterns have implications for service industries where employee retention directly affects operational costs and service quality. Practically, ‎hospitality managers should prioritize understanding employee psychological vulnerabilities over managing problematic colleagues, emphasizing person-environment fit during recruitment rather than conventional conflict resolution. These results advance social exchange theory ‎while offering novel retention strategies tailored to collectivist environments‎.